A SYSTEMATIC LITERATURE REVIEW ON FOOD WASTE AND SUSTAINABILITY (Third Sector Social Economic Review, 2025)
Food waste is one of the biggest and most complex problems encountered in the modern world. While millions of people around the world struggle with hunger and malnutrition, large amounts of food are wasted from production to consumption. This situation poses not only an economic loss but also a serious threat to environmental and social sustainability. The concept of sustainability has a central role in solving this problem. Preventing food waste is critical for protecting natural resources, reducing carbon footprints, and eliminating social inequalities. The aim of this research is to systematically examine how these two issues are addressed in the literature by addressing the concepts of food waste and sustainability, revealing the connections between them, and offering suggestions for future research. Data were obtained from the Web of Science database and analyzed using the VOSviewer program.Literature reviews emphasize that reducing food waste is of critical importance in terms of protecting natural resources, reducing carbon footprint and eliminating social inequalities. At the same time, it has been demonstrated that this waste is an area that will contribute to reducing global hunger and environmental sustainability in line with sustainable development goals.
Keywords: Food Waste; Sustainability; Food Safety; Food Packaging; VOSviewer